2022
DOI: 10.24875/ciru.20001246
|View full text |Cite
|
Sign up to set email alerts
|

Análisis epidemiológico de la depresión perinatal

Abstract: La depresión perinatal es un problema habitualmente subdiagnosticado que no sólo afecta de manera importante la salud mental y física materna, sino también al recién nacido en los aspectos físico, mental y cognitivo, con serias repercusiones en la vida adulta. A pesar de los esfuerzos para obtener información útil para dimensionar el problema, la mayoría de los expertos en el tema coinciden en señalar que este trastorno es más frecuente de lo que se estima. La mejora en la obtención de información en salud men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Turning to educational level, it should be noted that 50% of the 24 patients reported a maximum level of high school studies, which is striking, since the bibliography usually mentions that the lower the level, the greater the probability of scoring above the cutoff, as pointed out by Morales et al (2004) and Chan-Vázquez (2012). In addition to this, it is not overlooked that a large part of the patients had middle school as top reached level, being an important point described by Contreras-Carreto et al (2022), who report that this situation is a risk factor with an OR of 5.61, specifically in Mexican population.…”
Section: Discussionmentioning
confidence: 91%
“…Turning to educational level, it should be noted that 50% of the 24 patients reported a maximum level of high school studies, which is striking, since the bibliography usually mentions that the lower the level, the greater the probability of scoring above the cutoff, as pointed out by Morales et al (2004) and Chan-Vázquez (2012). In addition to this, it is not overlooked that a large part of the patients had middle school as top reached level, being an important point described by Contreras-Carreto et al (2022), who report that this situation is a risk factor with an OR of 5.61, specifically in Mexican population.…”
Section: Discussionmentioning
confidence: 91%
“…Although in this study most of the women were found to be within normal parameters, there were 15% in states of depression; and almost 8% were found in moderate to severe states, which put the women at risk of suffering incapacity to perform in daily life as socially adapted persons for their family, work and coexistence. Routine screening for depression in pregnancy will be of great preventive importance, as has been suggested in recent studies (11).…”
Section: Discussionmentioning
confidence: 97%
“…In Mexico, it is one of the most prevalent mental disorders and the leading cause of disability (6). (6); and it has been reported that 2 out of 10 women have depression in pregnancy, which is not diagnosed in a timely manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las alteraciones de la salud mental en el periodo de puerperio son un problema de salud pública, ya que el 19-25% de las mujeres de países con una economía de bajos-medianos ingresos presentan depresión posparto con escaso diagnóstico precoz, produciendo discapacidad con alta carga de morbilidad, riesgo de suicidio, demencia y mortalidad prematura, que ocasionan alteraciones en el desarrollo emocional, cognitivo y social del recién nacido, ya que las madres no se encuentran en las mejores condiciones de brindar el cuidado que requiere los neonatos y más aún cuando estos se encuentran hospitalizados (Eappen et al 2018). La depresión posparto se puede presentar en cualquier tipo de parto y sin importar el número de gestaciones, en México el 30.7% de las mujeres presentan depresión en algún momento del periodo de gestación y hasta 1 año después del parto (Contreras et al 2022), en Ecuador la incidencia de depresión posparto es de 27% en Machala, en Cuenca el 34% y en Guayaquil el 39% (García et al 2020). En la evolución Chrzan-Dętkoś et al ( 2021) establecieron una tasa de remisión de la depresión posparto del 53% en 12 meses y el suicidio se evidenció como la segunda causa de mortalidad en el primer año posparto.…”
Section: Introductionunclassified